,,The Colours of the Rainbow” – The Pedagogical Message of the Erdélyi Muzéum (Training and Practice : Journal of Educational Sciences, 2012)
The press is one of the most effective way of transmitting views and ideas, therefore, I have chosen the journal „Erdélyi Muzéum”, published in 1814, as the topic of my research. The main focus of this journal is not on pedagogy but it contains some articles about it. My aim is to analyse these works and to demonstrate those pedagogical messages which were intended to reach our times. In my opinion, through an analysis of such a journal one can gain insight into the world of diverse ideas, which were written by different people. There are the title of my essay is „The Colours of the Rainbow”. Through the study of the works I would like to highlight that the educational thinkers of the journal wanted to.facilitate the state of pedagogy in Hungary and they did not just interpret the views of foreign scholars.